Protest Against Human Trafficking In Paulo Coelho's Eleven Minutes Novel (2003) : A Sociological Approach - AYU NINGSIH, MEDISTA; , Dr. M. Thoyibi, M.S; , Titis Setyabudi, S.S. M. Hum (2015)
This research paper aims at knowing protest against humans trafficking in Eleven Minutes novel by Paulo Coelho which is analyzed by using sociological approach. The objective of the research is to analyze the novel based on sociological approach proposed by Diana Laurenson and Alan Swingewood. The type of this research is descriptive qualitative. Data of the research are taken from primary and secondary data. The method of analyzing this data is descriptive analysis. Based on the sociological analysis, the author illustrates a sociological phenomenon which should make every effort to cope with the problem of life. The sociological phenomenon is shown by the struggle of Maria to survive in Switzerland after as fraud victim in humans trafficking. Maria uses her creativity to protest against humans trafficking.